Kajian Molekuler Daerah D-Loop Parsial DNA Mitokondria Kuda (Equus caballus) Asli Tengger - -, Yuriadi; Widayanti, Rini; Purwantoro, Aris; Rangga Tabbu, Charles (Jurnal Veteriner; Vol 11 No 1 (2010), 2010)
Tengger’s horse (Equus caballus) is a local Indonesian horse an originated from its ancestor in Java.As the population of Tengger’s horse is almost extinct it is important to conserve and increase the horsepopulation by in situ or ex situ conservation.The objective of this research was to study the moleculargenetic of partial D-loop of Tengger’s horse. Sequencing of PCR product, showed that the D-loop consistedof 319 nucleotides. The DNA was isolated from whole blood and amplified and sequenced using a publishedprimer sets. The sequence was aligned and compared with horse D-loop sequences available in Genebankusing Clustal W method in MEGA program version 4.0.2. Ten different nucleotide sites were found inTengger horse from (nucleotide no. 9, 52, 64, 69, 102, 117, 133, 170, 187 and 293). The genetic distanceanalised using Kimura 2-parameter model ranged between 0,0% and 3,2%, with the average of 1,7%. Thephylogenetic tree using neighbor joining method based on the sequence of nucleotide partial D-loop couldnot be used to differentiate among horse from Tengger and E. caballus.
Keywords: Equus caballus , PCR, Tengger’s horse, Sequence Controle Region D-Loop